LOUW, A.J. (Ds.) Inventory of documents - LOUW, A.J. (Ds.) (ARCA, 2018)
Secretary of the National Party SWA; Member of the Legislative Assembly since April 1970; Letters regarding postage (16 dd 1903 and 3 dd 1924/1925)
COVERAGE: 0.10 metres
Keywords: LOUW, A.J. (Ds.); Inventories; Politicians; National Party; South West Africa